Growth Accounting for a Follower-Economy in a World of Ideas: The Example of Singapore - HO, Kong Weng (Institutional Knowledge at Singapore Management University, 2006)
In this paper, we take another approach to accounting for the sources of Singapore’s economic growth by being explicit about the channels through which Singapore, as a technological follower, benefits from international R&D spillovers. Taking into account the channels through which technology developed in the G5 countries diffuses to technological followers, we show that 57.5 percent of Singapore’s real GDP per worker growth rate over the 1970-2002 period is due to multifactor productivity growth. In particular, about 52 percent of the growth is accounted for by an increase in the effectiveness of accessing ideas developed by the technology leaders through improvement in our educational quality and increase in machinery imports and foreign direct investment from the G5 countries. We also find that capital accumulation that takes the form of imports of machinery as well as foreign direct investment from the G5 countries enhances the effectiveness of technology transfer thus raising the rate of return to capital. Compared to the rate of return to capital inferred from the traditional Solow growth model with purely exogenous technological progress of 10.8 percent, taking into account the technology transfer channel raises the implied rate of return to 13 percent